The Summers readers: first reader - Summers, Maud; Griffin, Marion Mahony, 1871-1961; Perkins, Lucy Fitch, 1865-1937 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Summers Readers: First Reader" by Maud Summers is a children$1 (Bs reader published in the early 20th century. This book is designed for young learners, introducing them to basic reading through a collection of simple stories and poems. The likely topic of the book revolves around moral lessons, nature, and childhood experiences, presented in an engaging manner to capture the interest of its young audience. The content of "The Summers Readers: First Reader" encompasses a variety of tales that promote moral values and an appreciation for nature. Stories such as "The Little Red Apple" and "The Wind and the Sun" illustrate themes of cooperation, honesty, and the strength found in kindness. Fables like "The Lion and the Mouse" and "The Three Little Pigs" teach lessons on friendship, cleverness, and resilience. The beautifully illustrated pages complement the text, making it visually appealing and accessible. Additionally, the poems interspersed throughout encourage a love for rhythmic language and storytelling, making this book a delightful first reader for children beginning their literacy journey. (This is an automatically generated summary.)s
Release date is 2022-02-02
Chuck Greif, hekula03 and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Readers (Primary)